Africa policy of the USA in Donald Trump era: Differences, expectations and realities - Aydın, Hasan (Cappadocia Journal of Area Studies, 2021)
In this study, Africa policy of the USA in the Donald Trump era is evaluated. The background of the study is the "Africa Strategy" declared by Trump's former National Security Advisor John Bolton at Heritage Foundation at the end of 2018. In this context, it is questioned whether the objectives of "increasing trade, behaving selective in foreign aids, fighting terrorism effectively, and balancing rival actors such as China" set forth in the strategy are successful. Throughout the study, the Trump administration's Africa policy is compared with its predecessors, the George W. Bush and H. Barack Obama administrations, and China, one of the most influential foreign actors on the continent. The final point reached in the study is that although some of the goals of the USA's Africa strategy announced during the Donald Trump period have been relatively achieved, the desired success has not been caught in general.